Effects of long-term 2.65 GHz radiofrequency radiation on inflammatory response and intestinal microbiota in mice - LI Keqin; LI Keqin; HAO Yanhui; LIU Ying (陆军军医大学学报)
Objective‍　‍To investigate the effects of long-term radiofrequency (RF) radiation at 2.65 GHz on behavior, inflammatory response, and intestinal microecology in mice in order to provide a basis for the safety assessment of long-term RF exposure. Methods‍　‍One hundred and eight male C57BL/6N mice (17~21 g, 6~8 weeks old) were randomly assigned to a control group (Con) and a RF exposure group. The mice of the RF exposure group were subjected to whole-body uniform exposure to 2.65 GHz RF radiation in an electromagnetic reverberation chamber for 3 h/day for 28 consecutive days. RF field distribution and changes in core body temperature were monitored using an electromagnetic radiation analyzer and a fiber-optic temperature probe, respectively. Cognitive function was assessed using the Y-maze and novel object recognition (NOR) test. Anxiety-like behaviors were evaluated through open field test (OFT) and elevated plus maze (EPM), while depressive-like behaviors were examined with sucrose preference test (SPT) and tail suspension test (TST). HE staining was used to observe the histopathological changes in mouse tissues. Radioimmunoassay (RIA) was employed to detect the expression of pro-inflammatory cytokines, TNF-α and IL-1β, as well as anti-inflammatory cytokines, IL-4 and IL-10 in the serum, brain, jejunum, and spleen samples. Additionally, metagenomic sequencing was performed to assess alterations in the gut microbiota composition. Results‍　‍Long-term RF radiation led to a maximal increase of 0.59 ℃ in the core body temperature, but had no significant effects on cognitive function, anxiety-like behaviors, or depressive-like behaviors, or apparent damage of the hippocampal or jejunal tissues in the exposed mice. However, RF exposure significantly up-regulated the expression of the pro-inflammatory cytokine TNF-α in serum (P<0.05), and did not significantly alter the concentrations of other cytokines (IL-1β，IL-4，IL-10), caused significant decrease in α-diversity of the intestinal microbiota (P<0.01), with reduced relative abundances of Ligilactobacillus murinus and Acetatifactor muris (P<0.05), while elevated abundances of Lachnospiraceae bacterium (P<0.01). Conclusion‍　‍Long-term exposure to 2.65 GHz RF radiation induces systemic inflammatory responses and disrupts gut microbiota homeostasis in mice.